PENGARUH FANATISME, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN OFFICIAL MERCHANDISE KLUB SEPAK BOLA PERSEBAYA SURABAYA - Noviany, Lintang; Dwi Rakhmawati, (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
In the modern era of the sports industry, football has evolved beyond mere entertainment into a highly profitable business sector, particularly through the sale of official merchandise. Persebaya Surabaya, one of the football clubs with the largest supporter base in Indonesia, has seized this opportunity through the establishment of the Persebaya Store. However, the widespread circulation of counterfeit products sold at lower prices presents a significant challenge. This study aims to examine the extent to which fanaticism, product quality, and price influence consumers’ decisions to purchase official Persebaya merchandise. A quantitative research approach was employed, with primary data collected through online questionnaires distributed to Persebaya supporters aged 17 and above who have purchased official merchandise at least twice. A purposive sampling technique was used, yielding a total of 101 respondents. The collected data were analyzed using multiple linear regression with the assistance of IBM SPSS version 30. The research results show that, partially, fanaticism and price influence purchasing decisions, while product quality shows no effect. Collectively, these three variables are proven to influence purchasing decisions.